Hubungan Tingkat Stres Dengan Kualitas Tidur Pada Mahasiswa Keperawatan Tingkat I dan IV Di Universitas Ichsan Satya - Rivani, Beata; Putri, Suzanna Fabella; Anggraini, Dewi; Eriawati, Eriawati (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
Introduction: Sleep is a basic physiological need for humans. Inadequate sleep can result in poor sleep quality. Factors that affect sleep quality are emotional stress, lifestyle, and environment. Stress is known to be associated with sleep patterns. Because during stress there will be an increase in the hormone epinephrine, cortisol hormone, and norepinephrine hormone which triggers the activity of the sympathetic nervous system which can cause sleep disturbances. Objective: To identify the relationship between stress level and sleep quality of nursing students level I and IV at Ichsan Satya University. Method: This type of research is quantitative observational with a cross-sectional approach. The research sample was grade I and IV students with a sampling technique using the Stratified Random Sampling technique, with 60 respondents from a total population of 158 level I and IV students at Ichsan Satya University. Results: The research analysis showed that at level I 43% of respondents experienced moderate stress and as many as 28% of respondents experienced poor sleep quality. Whereas at level IV 35% of respondents experienced moderate stress and as many as 37% of respondents experienced poor sleep quality. Chi-square test analysis obtained a p-value of 0.012 (<0.05) indicating that there is a significant relationship between stress levels and sleep quality in level I and IV nursing students at Ichsan Satya University. Conclusion: There is a relationship between stress level and sleep quality in nursing students level I and IV at Ichsan Satya University. Suggestion: for students it is hoped that when they are stressed they can divert stress with positive activities so that stress is not prolonged so that it affects sleep quality.